Metode Ceramah dan Media Leaflet terhadap Pengetahuan Ibu dalam Pencegahan ISPA - Sondang Sidabutar Sidabutar; Candra Johan Waruwu (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2022)
Acute infectious disease (ARI) that attacks one part and or more of the respiratory tract from the nose (upper tract) to the alveoli (lower tract) including adnexa such as sinuses, middle ear cavity and pleura. ARI is a disease that often occurs in children, because the child's immune system is still low. This study aims to determine the effect of health education with the lecture method and leaflet media on increasing maternal knowledge about the prevention of ARI (Acute Respiratory Infection) in the working area of ​​UPT Puskesmas Hiliduho. This type of research is quantitative research with a quasi-experimental research design. The design used was pretest and posttest group design without control group. The location of the research was carried out in the working area of ​​the Hiliduho Health Center, Hiliduho District, Nias Regency. The time of this research was carried out in August 2021. The population in this study amounted to 389 people. The sample in this study was determined by purposive sampling technique. The number of samples is 80 people. The difference in the mean knowledge of mothers before and after the lecture method health counseling was known to have a significant value from the t test for the respondents in the lecture group, namely p = 0.000 (p lebih kecil 0.05). The mean value of the respondent's knowledge before the lecture intervention was 1.98 while the mean value of the respondent's knowledge after the lecture was 1.18. The difference in the mean knowledge of mothers before and after the leaflet media health counseling was p = 0.000 (p lebih kecil 0.05). The mean value of respondents' knowledge before leaflet intervention was 5.68 while the mean value of respondent's knowledge after leaflet was 12.90.